Potensi Pengembangan Tanaman Anggrek di Kota Tomohon - Tirsa Onibala; Lyndon R.J. Pangemanan; Johnny A. Tuyuwale; Martha M. Sendow (COCOS, 2013)
ABSTRACTTIRSA ONIBALA. Orchid Plant Development Potency in Tomohon City. Under guidance of Lyndon R.J. Pangemanan as chairman, Johnny A. Tuyuwale and Martha M. Sendow as members.The objective of this research is to determine the potential for development of orchid plants in Tomohon. The data used in this study are primary and secondary data. The method used is purposive sampling where the respondent is orchid businessman. Under these conditions, three orchids businessman in Tomohon is selected. Data analysis performed in this study is a descriptive analysis, through the efforts of the description of any existing variable. The further calculation of benefits employers orchids, and to see the business proper of orchids by using comparative analysis of revenue and expenses (Revenue Cost Ratio).The research results showed that the potential factors that encourage the development of orchid plants are species-diverse species of orchids, orchid plant seed availability, production, labor, strategic location, climatic suitability for orchid plant to growth, and profit acquired by businessman orchids. Respondents 1 to obtain acceptance of Rp 17,980,000.00 with a total cost of Rp 14,034,792.00 and profits of Rp 3,945,208.00, respondents2to obtainacceptanceof Rp6,900,000,00with a total costof Rp3.306.000,00 and aprofit of Rp 3.594.000,00andrespondents3earnrevenueof Rp9.450.000,00with a total costof Rp3.261.200,00toprofitof Rp 6.188.800,00. Of the three respondent sentrepreneurs orchidsin Tomohonearnan profit average of Rp4.576.002,67.The Highest revenue cost ratio was respondent 3 with ratio 2.89, and the lowest was respondents 1 with ratio 1.28. Revenuecost ratiofromeachrespondentwas >1meansthat orchidbusiness was benefit.